Discrimination between beers with different best before dates using gas chromatography with mass spectrometry - Alex, Silky Alexis (2025)
The quality of beer is influenced by various factors, including its best-before dates, which may impact its flavour, aroma, and chemical composition. This study aimed to discriminate between beer samples from different best-before dates and different brands using liquid-liquid extraction followed by gas chromatography with mass spectrometry (LLE/GC-MS). In this study, beer samples from the brand Carlsberg® were selected to represent different time points with varying best-before dates to compare for their GC profiles. Additionally, four beer samples originated from different brands, namely Carlsberg®, Asahi®, Heineken® and Tiger® were also analysed and compared for their compositional differences. The GC-MS method was optimised for solvent selection, dissolution ratio, and injection volume to maximize detection sensitivity and accuracy, followed by the analyses of beer samples. Key findings through GC-MS revealed that beers with varying best-before dates exhibited distinct differences in their chemical profiles. Overall, 35 organic compounds were identified from Carlsberg® beer sample using the proposed method. Specific profiles for each beer set and from different brands were observed and visualised through principal component analysis. To conclude, this study has successfully determined the chemical profiles of beers with different best-before dates and of different brands, allowing for forensic discrimination of stale beer samples